First occurrence of feline sporotrichosis in a metropolitan area of Central-West Brazil - Ferreira, Mariana Almeida; de Paula Castilho, Allana; Vargas, Gabrielle Silveira; Patini, Bruna Elisa; Moreira, André Luís Elias; Santos, Jandra Pacheco dos; Xavier, Roseli Santos de Freitas; Del Negro, Gilda Maria Barbaro; Taborda, Carlos Pelleschi; Gremião, Isabella Dib; Ferreira Júnior, Álvaro (Revista do Instituto de Medicina Tropical de São Paulo, 2024)
Sporotrichosis is a neglected mycosis that affects human and animal hosts, including domestic cats. In Brazil, its most frequently diagnosed etiological agent is Sporothrix brasiliensis. Zoonotic transmission of S. brasiliensis occurs via direct contact between an infected cat and a susceptible human host. Notification of confirmed cases of feline sporotrichosis is not mandatory in Brazil. The metropolitan area of Goiania city can be considered a silent area for the occurrence of feline sporotrichosis. In this context, voluntary reporting of feline sporotrichosis cases is recommended for all healthcare professionals. This study aimed to report the first occurrence of S. brasiliensis in a cat from the metropolitan area of Goiania city. Cytopathology, mycology, thermal dimorphism and calmodulin gene amplification tests were performed. The mycological and molecular biological diagnoses corresponded to S. brasiliensis. The etiological agent of zoonotic sporotrichosis was detected in the metropolitan area of Goiania city, and therefore there is a risk of the emergence of new cases of cats infected with S. brasiliensis and the occurrence of zoonotic transmission of this fungus.